Respostas
respondido por:
3
complemento: ( 90º - x ) suplemento: ( 180º - x ) logo,
(90º - x) + (180º - x) = 190º . eliminando os parênteses
90º - x + 180º - x = 190º ⇒ - 2 x = 190] - 90º - 180º ⇒ - 2 x = - 80 .(-1)
2 x = 80º x = 80º : 2 ⇒ x 40º
Esse ângulo mede 40º
(90º - x) + (180º - x) = 190º . eliminando os parênteses
90º - x + 180º - x = 190º ⇒ - 2 x = 190] - 90º - 180º ⇒ - 2 x = - 80 .(-1)
2 x = 80º x = 80º : 2 ⇒ x 40º
Esse ângulo mede 40º
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás